2004
DOI: 10.1103/physrevlett.93.078101
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Phase Diagram of DNA Unzipping in the Temperature-Force Plane

Abstract: We separate double stranded lambda phage DNA by applying a fixed force at a constant temperature ranging from 15°C to 50°C, and measure the minimum force required to separate the two strands, providing the first experimental determination of the phase boundary between single stranded DNA and double stranded DNA in the temperatureforce plane. The measurements also offer information on the free energy of dsDNA at temperatures where dsDNA does not thermally denature in the absence of force. While parts of the pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
114
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(125 citation statements)
references
References 30 publications
10
114
1
Order By: Relevance
“…SI confirm that these DNA constructs had no nicks. Finally, a bead bound to a DNA molecule that is fully unzipped can remain bound only if there are no nicks in either backbone and several publications have shown that DNA treated using the techniques described in this paper can be completely unzipped (18,30,31). We also note that prior interpretations of overstretching studies have sometimes suggested that nicks exist and affect measurements (17,25,32,33).…”
Section: Methodsmentioning
confidence: 90%
“…SI confirm that these DNA constructs had no nicks. Finally, a bead bound to a DNA molecule that is fully unzipped can remain bound only if there are no nicks in either backbone and several publications have shown that DNA treated using the techniques described in this paper can be completely unzipped (18,30,31). We also note that prior interpretations of overstretching studies have sometimes suggested that nicks exist and affect measurements (17,25,32,33).…”
Section: Methodsmentioning
confidence: 90%
“…Squares correspond to the experimental results of [14]. Circles represent PBD simulations [19] [14], the theoretical result obtained with a popular thermodynamic model (green line) [14], together with our results (circles) from the described PBD simulations [19]. All results are related to the unzipping of λ-phage DNA (see [14,19] for sequence details).…”
Section: Forced Unzipping Of Dnamentioning
confidence: 99%
“…A first step towards understanding the relation between thermal denaturation and force-induced separation was taken by Danilowicz et al [14], who recently published the first experimentally determined phase diagram for DNA denaturation as a function of the applied force. The experimental data of this study confirmed intuition in the sense that the force required to unzip the DNA must decrease with increasing temperature.…”
Section: Forced Unzipping Of Dnamentioning
confidence: 99%
See 2 more Smart Citations